The (M)other Tongue : Essays in Feminist Psychoanalytic Interpretation - Garner, Shirley N.; Kahane, Claire; Sprengnether, Madelon S. (Cornell University Press, 2019)
This timely and provocative collection of sixteen essays combines feminist and psychoanalytic approaches to literary theory and to the reading of literary texts. It demonstrates not only the ways in which psychoanalytic theory can illuminate traditional literary texts, but also the ways in which feminist theory can modify, enlarge, and in some instances transform the body of psychoanalytic literature.Treating psychoanalysis as a form of narrative as well as a method of interpretation, the editors have divided their collection into three sections: 1) interpretations of the relation between contemporary feminism and Freud; 2) rereadings of classic patriarchal texts in the light of psychoanalytic feminism; and 3) readings of texts by women writers that have subverted patriarchal structures and given authoritative new voice to the maternal figure. Many of the essays make original contributions to the current debate about the conjunction of Freud and feminism; others offer innovative readings of specific texts that illustrate the significance of that relation. The Introduction provides an up-to-date survey of feminist psychoanalytic theory and enumerates the central issues.Because of the diversity of critical perspectives it offers and the range of texts it considers, this rich and important book will attract a broad spectrum of readers.